Is low BMI associated with specific drug use among injecting drug users? - McIlwraith, F.; Betts, K.; Jenkinson, R.; Hickey, S.; Burns, L.; Alati, Rosa (Informa Healthcare, 2014)
Body mass index (BMI) of a sample of people who regularly inject drugs (N = 781) was examined to gauge the impact of specific types of drug use. Cross-sectional interviews were undertaken in 2010 as part of a national monitoring program funded by the Australian Government. Latent class analysis identified three groups of drug users, with heroin users at 3.4 times the risk of being underweight compared with amphetamine users, and amphetamine users were at almost twice the odds of being obese compared with lower level morphine users. Nutrition should play a part in harm minimization. © 2014 Informa Healthcare USA, Inc.